Towards social justice in the neoliberal bologna process - Kushnir, Iryna; Eta, Elizabeth Agbor (Emerald Publishing Limited, 2023)
The Bologna Process created the European Higher Education Area (EHEA), establishing comparable higher education structures within the EHEA member states, but the process has also been influential in countries outside of the EHEA. The map of the EHEA on the cover page of this book presents current active members of the EHEA, following EHEA membership changes in April 2022. Towards Social Justice in the Neoliberal Bologna Process combines research from leading international scholars. The eclecticism of the perspectives shed light on the interaction between neoliberal and social justice discourses in the Bologna Process by exploring neoliberal aspects of Bologna and the growing voice of social justice. The editors present these discourses as complementary rather than opposing, contrary to popular perspectives in the wider literature. Applying this lens to the analysis of a range of Bologna's action lines in the context of the EHEA and beyond is very important, particularly now. Identifying pitfalls in the social justice agenda in the Bologna Process calls for the attention of Bologna policymakers on the international level to address these issues in the run-up to the new 2030 EHEA deadline. This timely collection is essential reading for higher education scholars, policymakers, and postgraduate students across the EHEA, as well as countries beyond the EHEA that have been aligning their systems of education to the Bologna Process.
Keywords: Bologna process (European higher education); Social justice.; Education -- Educational Policy & Reform -- General.; Educational strategies & policy.; elektronické knihy; electronic books